2019
DOI: 10.1021/acs.est.8b05012
|View full text |Cite
|
Sign up to set email alerts
|

In the Search for Nanospecific Effects of Dissolution of Metallic Nanoparticles at Freshwater-Like Conditions: A Critical Review

Abstract: Knowledge on relations between particle properties and dissolution/transformation characteristics of metal and metal oxide nanoparticles (NPs) in freshwater is important for risk assessment and product development. This critical review aims to elucidate nanospecific effects on dissolution of metallic NPs in freshwater and similar media. Dissolution rate constants are compiled and analyzed for NPs of silver (Ag), copper (Cu), copper oxide/hydroxide (CuO, Cu­(OH)2), zinc oxide (ZnO), manganese (Mn), and aluminum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
45
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(52 citation statements)
references
References 169 publications
(492 reference statements)
2
45
0
1
Order By: Relevance
“…Dissolution of ENMs can be considered as chemical transformation processes of ENMs from particulate forms into dissolved ions as shown in Figure 1 . Dissolution is particularly relevant for metallic and metal oxide ENMs, such as AgNPs, ZnO NPs, and copper oxide nanoparticles (CuO NPs), which have been shown to dissolve to Ag + , Zn 2+ , and Cu 2+ , respectively, in aqueous solutions [ 83 , 84 , 85 , 86 , 87 ]. In contrast, metal oxide nanoparticles, such as TiO 2 NPs, CeO 2 NPs, and silicon dioxide nanoparticles (SiO 2 NPs), are fairly insoluble in environmental waters [ 31 ].…”
Section: Engineered Nanomaterials (Enm) Fate Processes In Surface Wmentioning
confidence: 99%
See 3 more Smart Citations
“…Dissolution of ENMs can be considered as chemical transformation processes of ENMs from particulate forms into dissolved ions as shown in Figure 1 . Dissolution is particularly relevant for metallic and metal oxide ENMs, such as AgNPs, ZnO NPs, and copper oxide nanoparticles (CuO NPs), which have been shown to dissolve to Ag + , Zn 2+ , and Cu 2+ , respectively, in aqueous solutions [ 83 , 84 , 85 , 86 , 87 ]. In contrast, metal oxide nanoparticles, such as TiO 2 NPs, CeO 2 NPs, and silicon dioxide nanoparticles (SiO 2 NPs), are fairly insoluble in environmental waters [ 31 ].…”
Section: Engineered Nanomaterials (Enm) Fate Processes In Surface Wmentioning
confidence: 99%
“…Water chemistry factors also affect the dissolution of ENMs. Generally, decreased pH increases the dissolution of metallic and metal oxide ENMs [ 83 , 84 , 85 , 86 , 87 ]. Additionally, agglomeration of ENMs tends to diminish the dissolution rate by reducing the diffusion of species involved in dissolution reactions [ 82 , 87 ].…”
Section: Engineered Nanomaterials (Enm) Fate Processes In Surface Wmentioning
confidence: 99%
See 2 more Smart Citations
“…Both carbon-based and metal-based nanoparticles are of concern and it has been reported these particles are persistent in water [214,215]. Nanomaterial transformation in fresh water systems is an active field of research [216]. Nanoparticle assessments have concluded that fine particulate matter occurs in a variety of water sources [217][218][219][220][221], so its impact on irrigation water, accumulation in soil, and potential for crop uptake is of paramount significance.…”
Section: Engineered Nanomaterialsmentioning
confidence: 99%